Block periodization of strength and endurance training is superior to traditional periodization in ice hockey players - Ronnestad, B. R.; Ofsteng, S. J.; Ellefsen, S. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Team sports like ice hockey require high levels of performance in numerous physical characteristics such as strength, power, and endurance. As such, training is associated with a potential interference effect. The present study randomized well-trained ice hockey players into a block periodization group (BP; n = 8), focusing on the development of either strength and power or endurance on a weekly, undulating basis, and a traditional group (TRAD; n = 8), performing a mixed training model, with simultaneous focus of strength, power, and endurance training every week. During the 6-week intervention, the two groups performed equal volumes and intensities of both strength, power, and endurance training. BP led to larger improvements than TRAD in knee extension peak torque at 180° s-1 (6.6 ± 8.7 vs -4.2% ± 6.3%, respectively; P< 0.05) and maximal oxygen uptake (5.1 ± 3.3 vs 1.1% ± 3.5%, respectively; P< 0.05). There was also a trend toward larger improvements in BP than TRAD in peak torque in knee extension at 60° s-1 (2.1 ± 2.5 vs -0.1% ± 2.5%, respectively; P< 0.1, effect size = 0.83) and mean power output during a 30-s cycling sprint (4.1 ± 2.5 vs -0.3% ± 5.9%, respectively; P< 0.1, effect size = 0.89). Overall, BP exhibited a moderate to large effect size for all these variables compared to TRAD. The present study suggests that block periodization of strength and endurance training induces superior adaptations in both strength and endurance capacities in welltrained ice hockey players compared to traditional mixed organization, despite similar training volume and intensity. Abstract from author